Makna Simbolik Properti Tari Grombyang Pemalang di Sanggar Seni Kaloka Pemalang - Annisa Yuriskia Fadilla; R. Indriyanto (Lembaga Pengembangan Kinerja Dosen, 2026)
This study is motivated by the limited public understanding of the symbolic meaning of properties used in the Grombyang Dance of Pemalang, where most audiences merely enjoy the performance without recognizing the cultural values embedded within it. This research aims to examine and explain the symbolic meanings of the properties used in the Grombyang Dance of Pemalang as performed at Sanggar Seni Kaloka Pemalang. The method employed is a descriptive qualitative approach using semiotic analysis based on Charles Sanders Peirce, with data collection techniques including observation, interviews, and documentation. The results of the study indicate that the performance structure of the Grombyang Dance of Pemalang consists of three main parts: the opening, the core, and the closing, supported by various elements such as theme, movement, performers, makeup, costume, musical accompaniment, stage setting, and properties. The semiotic analysis reveals that the symbolic meaning of the properties can be understood through the relationship between representamen, object, and interpretant. The main property, the irus (ladle), functions as a symbol that not only represents the act of scooping Grombyang soup but also carries a belief-related meaning as a bringer of fortune in trading activities. In conclusion, the properties in the Grombyang Dance of Pemalang serve not only as aesthetic elements but also as a medium of symbolic communication that reflects cultural, social, and belief values within the community. Therefore, they are important to be preserved and more deeply understood by the public.